Weak Scattering of Young's Diffractive Light Wave From a Spatially Deterministic Medium - Jia Li; Feinan Chen; Liping Chang (IEEE Photonics Journal)
We study the modeling of the scattering of Young's diffractive light wave from a 3-D medium of which the refractive index is a deterministic function of position. Within the validity of the first-order Born approximation, the spectral density of the scattered field is derived as the analytic form. It is shown that the scattering angle and effective radius of the scattering potential account for the substantial effects on the spectral density profiles of the scattered field. It is also revealed that Young's pinhole parameter can affect the spectral density distribution of the scattered field. Our findings may be significant for the determination of structural parameters of an unknown scatterer.